Functional AGXT2 SNP rs37369 Variant Is a Risk Factor for Diabetes Mellitus: Baseline Data From the Aidai Cohort Study in Japan - Kumon, Hiroshi; Miyake, Yoshihiro; Yoshino, Yuta; Iga, Jun-ichi; Tanaka, Keiko; Senba, Hidenori; Kimura, Eizen; Higaki, Takashi; Matsuura, Bunzo; Kawamoto, Ryuichi; Ueno, Shu-ichi (Canadian journal of diabetes, 2022)
The relationship between alanine-glyoxylate aminotransferase 2 (AGXT2) single-nucleotide polymorphisms (SNPs) and diabetes mellitus (DM) has not been investigated. Therefore, we performed a case–control study to examine this relationship. The study subjects included 2,390 Japanese men and women aged 34 to 88 years. In total, 190 cases were defined as having a fasting plasma glucose level ≥126 mg/dL, having a glycated hemoglobin ≥6.5% or currently using diabetic medication. The 2,200 remaining participants served as control subjects. Compared with study subjects with the CC genotype of AGXT2 SNP rs37369, those with the TT, but not CT, genotype had a significantly increased risk of DM: the adjusted odds ratio (OR) for the TT genotype was 1.83 (95% confidence interval [CI], 1.04 to 3.47). AGXT2 SNPs rs37370 and rs180749 were not significantly associated with the risk of DM. The CTA haplotype of rs37370, rs37369 and rs180749 was significantly positively associated with the risk of DM (crude OR, 1.25; 95% CI, 1.01 to 1.56), whereas the CCA haplotype was significantly inversely related to DM (crude OR, 0.53; 95% CI, 0.27 to 0.95). The multiplicative interaction between AGXT2 SNP rs37369 and smoking status with regard to the risk of DM was not significant (p=0.32 for interaction). This is the first study to show significant associations between AGXT2 SNP rs37369, the CTA haplotype, and the CCA haplotype and DM. No interaction with regard to the risk of DM was observed between rs37369 and smoking. La relation entre les polymorphismes mononucléotidiques (PMN) dans l’alanine-glyoxylate aminotransférase 2 (AGXT2) et le diabète sucré (DS) n’a pas fait l’objet d’études. Par conséquent, nous avons réalisé une étude cas témoins pour examiner cette relation. Les sujets de l’étude étaient 2390 femmes et hommes japonais de 34 à 88 ans. Au total, nous avons recensé 190 cas qui avaient des concentrations plasmatiques de glucose à jeun ≥ 126 mg/dl, une hémoglobine (A1c) ≥ 6,5 % ou qui utilisaient actuellement des médicaments contre le diabète. Les 2200 participants restants constituaient les sujets témoins. Comparativement aux sujets de l’étude qui avaient un génotype CC de PMN rs37369 dans l’AGXT2, ceux qui avaient le génotype TT, mais non le génotype CT, avaient un risque significativement accru de DS : le rapport de cotes (RC) ajusté du génotype TT était de 1,83 (intervalle de confiance [IC] à 95 %, de 1,04 à 3,47). Les PMN rs37370 et rs180749 dans l’AGXT2 n’étaient pas associés de façon significative au risque de DS. L’haplotype CTA du rs37370, du rs37369 et du rs180749 était de façon significative associé positivement au risque de DS (RC brut, 1,25; IC à 95 %, de 1,01 à 1,56), alors que l’haplotype CCA était de façon significative relié inversement (RC brut, 0,53; IC à 95 %, de 0,27 à 0,95). Quant au risque de DS, l’interaction multiplicative entre le PMN rs37369 dans l’AGXT2 et le tabagisme n’était pas significative (valeur p de l’interaction = 0,32). Il s’agit de la première étude à démontrer les associations significatives entre le PMN rs37369 dans l’AGXT2, l’haplotype CTA et l’haplotype CCA, et le DS. Quant au risque de DS, aucune interaction n’a été observée entre le rs37369 et le tabagisme.